The Impact of the Consumption of Moringa Leaf on the Production of Postpartum Breast Milk in Puskesmas III Denpasar Selatan Working Area Mothers - Ade Dwidya Pradnyani; Luh Putu Widiastini; Ni Putu Yunita Sri Lestari (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
A dietary item that is high in nutrients is moringa (moringa oleifera). Many phytosterols found in moringa leaves can help boost the production capacity of breast milk. The motivation behind the research was to find out how eating moringa leaves affected the quantity of breast milk produced by new moms in the Puskesmas III Denpasar Selatan Working Area. The investigation's design involves a control group plus a pre-post test, utilizing a quasi-experimental methodology. 40 people made up the sample, which was selected by random sampling. using the Mann-Whitney and Wilcoxon tests to analyze descriptive and comparative data. After the intervention, the average research results were 1.2 (fluent) with a p-value of 0.001 < 0.05, showing that the consumption of the Moringa leaf intervention altered the average amount of breast milk produced by the control group. Prior to the intervention, the average research results were 1.85 (not fluent). The mean in the control group did not change before or after giving one glass of water prior to breastfeeding; the mean was 1.80 (incoherent) before the intervention and 1.65 (incoherent) after it. This is supported by the p-value of 0.083 > 0.05. Conclusion: In the Puskesmas III Denpasar Selatan work region, postpartum women's production of breast milk is impacted by their use of moringa leaves. Moringa leaves can help postpartum moms whose breast milk isn't flowing easily produce more of it.